Host and disease factors are associated with cognitive function in European HIV‐infected adults prior to initiation of antiretroviral therapy. Issue 6 (26th November 2015) - Winston, A; Stöhr, W; Antinori, A; Arenas‐Pinto, A; Llibre, JM; Amieva, H; Cabié, A; Williams, I; Di Perri, G; Tellez, MJ; Rockstroh, J; Babiker, A; et al.
Abstract : Objectives: Deficits in cognitive function remain prevalent in HIV‐infected individuals. The aim of this European multicentre study was to assess factors associated with cognitive function in antiretroviral therapy (ART)‐naïve HIV‐infected subjects at the time of enrolment in the NEAT 001/Agence Nationale de Recherche sur le SIDA (ANRS) 143 study. Methods: Prior to starting ART, seven cognitive tests exploring domains including episodic memory, verbal fluency, executive function and psychomotor speed were administered with scores standardized to z ‐score using the study population sample mean and standard deviation. The primary measure was overall z ‐score average (NPZ). We assessed associations between baseline factors and test results using multivariable regression models. Results: Of 283 subjects with baseline cognitive assessments, 90% were male and 12% of black ethnicity. Median (interquartile range) age, years of education, years of known HIV infection, baseline CD4 count and baseline HIV RNA were 39 (31, 47) years, 13 (11, 17) years, 1 (0, 4) years, 344 (279, 410) cells/μL and 4.74 (4.28, 5.14) log10 HIV‐1 RNA copies/mL, respectively. Forty per cent were current smokers. Factors significantly associated with poorer overall cognitive performance in multivariable models included older age, shorter duration of education, black ethnicity, lower height, and lower plasma HIV RNA. Conclusions: In this large, European‐wide, ART‐naïve population with relatively preserved immunity and early HIV infection, cognitive function scores at the time of ART initiation were associated with demographic and HIV‐disease factors.